1986
DOI: 10.1042/bj2360149
|View full text |Cite
|
Sign up to set email alerts
|

The influence of N-acetylneuraminic acid on the properties of human orosomucoid

Abstract: Little is known of the relationships that may exist among the three principal functionalities of glycoproteins. Orosomucoids of closely defined N-acetylneuraminic acid content were examined for evidence of influence of N-acetylneuraminic acid content on the physical properties of the glycoprotein. Fluorescence spectroscopy gave no indication of conformational change in the protein core upon desialylation. Small changes in the chromatographic partition coefficient, sigma, and thermal stability, Td, are interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
2
17
1
Order By: Relevance
“…Although there was no detectable change in the trypsin susceptibility or Stern-Volmer constant upon removal of sialic acids from GdA, GdA lost significant anti-proliferative activity. Sialic acid-dependent modulation of activity has been reported previously (27,30). We also observed a reduction of the hydrodynamic volume after removal of sialic acids from GdA.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Although there was no detectable change in the trypsin susceptibility or Stern-Volmer constant upon removal of sialic acids from GdA, GdA lost significant anti-proliferative activity. Sialic acid-dependent modulation of activity has been reported previously (27,30). We also observed a reduction of the hydrodynamic volume after removal of sialic acids from GdA.…”
Section: Discussionsupporting
confidence: 68%
“…However, desialylation of GdA decreased its hydrodynamic volume to a value close to that of GdS (Table II). Such a change in hydrodynamic volume upon removal of sialic acids has been reported for another lipocalin, ␣ 1 -acid glycoprotein (27). Reversion of the hydrodynamic volume of desialylated GdA to a value close to that of GdS suggests that the addition of sialic acids exposes an apoptogenic region on the glycodelin backbone that is masked in their absence.…”
Section: Discussionmentioning
confidence: 86%
“…It is also evident from Table 4 that the AGPphenothiazine system gave higher binding affinities than the asialoAGP-phenothiazine system, particularly for chlorpromazine. A similar large difference in binding constants of chlorpromazine to AGP and asialoAGP was also found by Friedman et al (1986). As the isoelectric points of AGP and asialoAGP were about 2.9 and 4.5, respectively, at pH 7.4, AGP would contain more negative charges than asialoAGP (Kremer et a1 1988).…”
Section: Discussionmentioning
confidence: 53%
“…Our results confirm that this protein has the same overall folding as the F1*S variant. The carbohydrate groups on hAGP are thought to have little effect on drug-binding properties and secondary structure (33,34). Our previous findings also demonstrated that the drug-binding capacity of a mutant, C149R, was equivalent to that of the A form purified from serum (35).…”
Section: Discussionmentioning
confidence: 61%